ON SOME ASPECTS OF THE ORGANIZATION OF EDUCATIONAL WORKS OF TECHNICAL STUDENTS UNIVERSITIES - R.B. Lysenko (Academy of Cognitive and Natural Sciences, 2022)
In the article some ways of further perfection of technical universities' students' educational work taking into consideration new conditions of education are discussed.